Pengaruh Green Marketing Mix Terhadap Minat Beli Produk Sayur Hidroponik Di Kabupaten Bekasi Jawa Barat - Alaidin Rapani; Dhian Tyas Untari; Syahnan S Phalipi; Rudy Rudy; Fata Nidaul Khasanah; Budi Satria (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
Marketing is one of the main activities carried out by entrepreneurs in maintaining the continuity of their business, to develop and get profits. Now, this marketing concept has evolved along with the advancement of society and technology. So that the company's goal is to provide satisfaction to consumers in order to get profits. In connection with this, this research activity discusses the influence of green marketing mix strategies on the effectiveness of hydroponic vegetable sales volume. The study involved 100 Bekasi Regency people who had consumed and purchased hydroponic vegetable products. The conclusion that can be drawn is that green product, green price, green place and green promotion both partially and simultaneously affect the buying interest of the people of Bekasi Regency towards hydroponic vegetable products. There are differences in people's preferences, especially in Bekasi Regency, towards hydroponic vegetables based on the physical attributes of leaves, leaf color, taste, freshness, and packaging.